The Role of Word Play in Advertising Text (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
This article is devoted to the lexical features and role of the word play and the problems of ways in reproducing. The main difficulties associated with the transformation of a word play Moreover, the need to create original, memorable texts that can attract the attention of a potential costumer, the reasons for the interest of advertisers are investigated.The issue of word play is a multifaceted phenomenon that, performing a number of functions, occupies a special place in the texts of advertising. Wordplay is closely related to the content of the advertising and is used to attract the attention of a potential customer.